A Coincident Indicator of the Gulf Cooperation Council (GCC) Business Cycle - Al-Hassan, Abdullah (IMF Working Papers; Working Paper ;, 2009)
This paper constructs a coincident indicator for the Gulf Cooperation Council (GCC) area business cycle. The resulting coincident indicator provides a reliable measure of the GCC business cycle; over the last decade, the GCC coincident index and the real GDP growth have moved closely together. Since the indicator is constructed using a small number of common factors, the strong correlation between the indicator and real GDP growth points to a high degree of commonality across GCC economies. The timing and direction of movements in macroeconomic variables are characterized with respect to the coincident indicator. Finally, to obtain a meaningful economic interpretation of the latent factors, their behavior is compared to the observed economic variables.